Colaboração científica nos programas de pós-graduação em educação : uma análise de redes de coautoria - Oliveira, Walison Aparecido de (2017)
The present study has the objective to investigate the network conformation of scientific collaboration's postdegree program in Sducation located in Brazil's Southwest. Use it in two methodologies, the social media analysis and the bibliometry. The scientific production was collected in lattes plataform deriving from curriculum of accredited teachers in 15 postdegree programs. Considering datas by two last tests of CAPES (triennia 2007-9 2010-2). The bibliographic records was extracted between scriptlattes software. The Vantage Point® software and UCINET was used to systematization and analysis of the results. Found that the area published on average 60% of articles in collaboration and there is a decrease (5%) in articles with authors individual. there is a uniform distribution of articles between the strata Qualis, ranging from 10% to 15%. according to the Qualis area, 14% of articles not total score for the program. there is a diversity in the profile of collaboration of the programs, some have more than 70% of its production in collaboration, and others with a maximum of 40%. the protagonists in collaboration scientific are programs level 6 (ufscar-and and) and level 5 (ufscar). the level 7 and most of the level 6 do not appear prominently. there are no greater approach between teachers of the programs for publication, for having higher level. the higher the average articles by program, the greater the possibility of publication joint. specific areas of education with other areas of knowledge (psychology, health, biology, etc.), impact the shape of the scientific production.